Map-based uncertainty analysis for exploration using basin modeling and machine learning techniques applied to the Levant Basin petroleum systems, Eastern Mediterranean. (October 2020) - Ducros, Mathieu; Nader, Fadi Henri
Abstract: The Levant Basin of the East-Mediterranean region contains a biogenic petroleum system and possibly an underlying thermogenic system. The application of a new map-based uncertainty and sensitivity analysis that integrates a large set of geological parameters demonstrates that a connection between an Upper Cretaceous thermogenic petroleum system and the shallower Oligo-Miocene reservoirs is highly possible in the southern part of the basin (offshore Israel and southern Lebanon) where hydrocarbon fluids are generated from the Campanian source rock and charge the overlying Oligo-Miocene reservoir interval through faults. Estimates of volumes of expelled hydrocarbons combined with regional analysis of the Eocene top seal integrity indicates that the most prospective zones correspond to the southern offshore Lebanon and offshore Israel. In the northern part of the Levant Basin (offshore central and northern Lebanon), petroleum fluids potentially generated by the Campanian source rocks remain trapped under the Eocene seal or they migrate towards the margins of the basin. Our approach is based on applications of machine learning techniques and robust statistical analyses to petroleum systems modeling, focusing on spatial uncertainty analysis. It may be used on similar frontier or emerging hydrocarbon provinces to help de-risking the petroleum systems. Highlights: Use of machine learning and basin modeling for petroleum system risk assessment. Accurate map-based uncertainty analysis compatible with exploration workflows. Cretaceous thermogenic source rocks possibly connected to Oligo-Miocene reservoirs. The Southern Levant Basin is more favorable to such a connection. Further study on source rock reactivity could significantly reduce uncertainties.